Evidence from the resurrected family Polyrhabdinidae Kamm, 1922 (Apicomplexa: Gregarinomorpha) supports the epimerite, an attachment organelle, as a major eugregarine innovation - Paskerova, Gita G; Miroliubova, Tatiana S; Valigurová, Andrea; Janouškovec, Jan; Kováčiková, Magdaléna; Diakin, Andrei; Sokolova, Yuliya Ya; Mikhailov, Kirill V; Aleoshin, Vladimir V; Simdyanov, Timur G (PeerJ, 2021)
BACKGROUND: Gregarines are a major group of apicomplexan parasites of invertebrates. The gregarine classification is largely incomplete because it relies primarily on light microscopy, while electron microscopy and molecular data in the group are fragmentary and often do not overlap. A key characteristic in gregarine taxonomy is the structure and function of their attachment organelles (AOs). AOs have been commonly classified as "mucrons" or "epimerites" based on their association with other cellular traits such as septation. An alternative proposal focused on the AOs structure, functional role, and developmental fate has recently restricted the terms "mucron" to archigregarines and "epimerite" to eugregarines. METHODS: Light microscopy and scanning and transmission electron microscopy, molecular phylogenetic analyses of ribosomal RNA genes. RESULTS: We obtained the first data on fine morphology of aseptate eugregarines Polyrhabdina pygospionis and Polyrhabdina cf. spionis, the type species. We demonstrate that their AOs differ from the mucron in archigregarines and represent an epimerite structurally resembling that in other eugregarines examined using electron microscopy. We then used the concatenated ribosomal operon DNA sequences (SSU, 5.8S, and LSU rDNA) of P. pygospionis to explore the phylogeny of eugregarines with a resolution superior to SSU rDNA alone. The obtained phylogenies show that the Polyrhabdina clade represents an independent, deep-branching family in the Ancoroidea clade within eugregarines. Combined, these results lend strong support to the hypothesis that the epimerite is a synapomorphic innovation of eugregarines. Based on these findings, we resurrect the family Polyrhabdinidae Kamm, 1922 and erect and diagnose the family Trollidiidae fam. n. within the superfamily Ancoroidea Simdyanov et al., 2017. Additionally, we re-describe the characteristics of P. pygospionis, emend the diagnoses of the genus Polyrhabdina, the family Polyrhabdinidae, and the superfamily Ancoroidea.
Keywords: Phylogeny; Environmental DNA sequences; Host-parasite relationships; Eugregarinida; Intestinal parasites; Marine gregarines; Taxonomy; Ultrastructure; SSU and LSU rDNA